Dilemma of new entrepreneurs in fund-raising strategies - A. Rahman, Badruddin (ASEAN Universities Consortium of Entrepreneurship Education (AUCEE), 2010)
Venture capitalists (VCs) receive many business plans and proposals, sometimes 100 or more a month. However, they typically reject 98% of opportunities presented especially by young companies.Perhaps this may be due to the lack of understanding or the inability of entrepreneurs(of the young companies) to fulfill the three basic principles of entrepreneurial finance: (a) More cash is preferred to less cash (b) Cash sooner is preferred to cash later; and (c) Less risky cash is preferred to more risky cash. It is almost a pre-requisite for venture capital industry to supply capital and other required resources to entrepreneurs who are in high potential business, in hoping that a high rate of return on invested funds can be realized. Specifically. VCs' assessment of probability of survival is significantly higher for ventures facing high key success factor stability, that are late followers, have long lead times, low competitive rivalry, high educational capability, and high industry related competence. These factors may contribute to dilemma of new entrepreneurs in their fund-raising strategies.